PERANCANGAN TATA LETAK RELOKASI LANTAI PRODUKSI DENGAN METODE SYSTEMATIC LAYOUT PLANNING, BLOCPLAN, DAN FLAP - Halim, Gabrielle; Gozali, Lina; Kristina, Helena Juliana; Robin, Christhoper (Program Studi Teknik Industri, Fakultas Teknik Universitas Tarumanagara, 2024)
In the development of the industrial revolution 4.0, in carrying out production at small, medium, and large levels, there has been a fairly large and significant increase. Factors that influence the goal of successful production are not only about investment, capital, suppliers, machines, skills, and distributors but also one that must be observed is the layout planning and placement of factory facilities. PT. Eworx Indonesia is a company engaged in the processing industry, especially manufacturing in the metal processing sector. PT. Eworx Indonesia intends to relocate the production floor in order to increase production productivity. In this study, the proposed layout design on the new production floor was carried out using the SLP, Blocplan, and FLAP methods. The design is done by collecting direct observation data and interviews with the operator on duty. It was found that the initial layout had problems with operator movement that was not optimal and the placement of several machines and facilities that did not pay attention to material flow resulting in a slowdown in production time. Therefore, in order to get the best layout, a comparison is made on the results of the three alternative layouts with the smallest displacement distance comparison so that the production process will run more optimally. The best proposed layout is the systematic layout planning (SLP) method with the smallest material displacement distance of 147.4 meters and material handling costs Rp. 223,958 per day. Flexsim simulations show this layout can increase production output by 15%-34%.